The Effectiveness of Perovskia abrotanoides Extract Topical Formulation on the Cutaneous Leishmaniasis: A Randomized Controlled Clinical Trial - Maryam Sadat Tayebi; Nazila Poostiyan; Masoud Sadeghi Dinani; Erfaneh Ghassami; Rasool Soltani (Wolters Kluwer Medknow Publications, 2024)
Objective: Despite many attempts to treat leishmaniasis, new approaches are necessary to reduce the burden of disease. Perovskia abrotanoides (Brazambel) has shown significant effects against Leishmania parasites in some studies. This study aimed to investigate the effects of P. abrotanoides extract topical formulation on cutaneous leishmaniasis. Methods: In this randomized controlled clinical trial, patients with cutaneous leishmaniasis were assigned to experimental (n = 18) and control (n = 18) groups. Both groups received intralesional meglumine antimoniate (Glucantime®). The experimental group also received 5% Brazambel extract ointment once a day. The interventions continued until the complete healing of the lesions (reepithelialization) for a maximum of 8 weeks. The clinical response, defined as complete response (reepithelialization >75%), partial response (reepithelialization 50%- 75%), or treatment failure (reepithelialization <50%), was compared between the groups. Findings: The percentage of reepithelialization in the experimental group (4th week: 64.44 ± 25.13; 8th week: 83.85 ± 11.54) was higher than the control group (4th week: 53.97 ± 25.88; 8th week: 76.27 ± 21.67); however, the differences were not statistically significant (P = 0.252 and 0.494, respectively). Moreover, there was no significant difference between the experimental and control groups regarding the rate of complete healing (88.9% vs. 72.2%, respectively). Conclusion: The use of P. abrotanoides extract 5% topical formulation does not affect the healing of cutaneous leishmaniasis.